Representative Volume Element Homogenization of a Composite Material by Using Bond-Based Peridynamics - Xia, Wenxuan; Galadima, Yakubu Kasimu; Oterkus, Erkan; Oterkus, Selda (Journal of Composites and Biodegradable Polymers, 2019)
This study presents representative volume element (RVE) homogenization by using bond-based peridynamics. First, a method to perform RVE homogenisation analysis with bond-based peridynamic theory is demonstrated. Homogenized material properties of a unit-sized fibre reinforced composite cell with varying fibre volume fraction are predicted using the present method. Peridynamic results are compared against a finite element based RVE approach and a good agreement is observed between the two approaches.